Frequency of Congenital Heart Disease in Children with Heart Murmur at Teriary Care Hospital - Inam Ullah, Abid Imran, Sijad-Ur-Rehman, Romana Bibi, Muhammad Ishaq, Muhammad Idrees (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: To determine the frequency of congenital heart disease in children of age 2 months to 5 years with heart murmur. Methods: This Descriptive Cross Sectional was conducted in Pediatrics Unit, MTI-Hayatabad Medical Complex, Peshawar from February-August 2019. After ethical approval detailed clinical examination was performed with the help of a stethoscope. Auscultation was also be performed by a Pediatrician. For confirmation of congenital heart disease echocardiography, color doppler ultrasound and echocardiography were performed. Results: A number of congenital heart diseases were recorded in patients presented with heart murmur. Mean age of patients was 4.1+1.3 years, weight was 14.2+2.5 kg and for duration 1.2+0.6 years. 130(49.42%) patients were recorded in 2 months to 3 years age group whereas 133(50.57%) patients were recorded in 4 to 5 years age group. 196(74.52%) patients were male while 67(25.5%) patients were female. 29(11.02%) were diagnosed with PDA, 21(7.9%) patients were recorded with VSD, 18(6.84%) patients were recorded with ASD, 21(7.9%) patients were diagnosed for PFO while 33(12.5%) patients were having TGA. P-value of congenital heart disease with the duration of symptoms were calculated using chi-square test were PDA (p=0.716), VSD (p=0.816), ASD (p=0.762), PFO (p=0.603), TGA (p=0.557). Practical Implication: The practical implication of our study is to recommend proper evaluation, early management of children with heart murmur for CHDs in our local population. Conclusion: Children with CHD are more likely to have heart murmur as we recorded high prevalence of congenital heart diseases in children presented with heart murmur Keywords: Congenital Heart Disease, Congestive Heart Failure, Patent Ductus Arteriosus